The birthday party of no return! - Stine, R. L. (New York : Scholastic Inc., 2012)
"Lee Hargrove only wants one thing-to win a scholarship to Summer Sports Camp. His school is holding a competition and the winner gets to attend the camp for free. Lee is one of the favorites to win along with his friend Corey "Lucky Duck" Duckworth and another athletic classmate, Laura Grodin. Laura is good...for a girl, but how can anyone compete with Corey's good-luck streak? Lee has an idea and he's about to give Corey an unforgettable birthday present that will really get the party started!"--P. 4 of cover.
edited hb 2015-06-16
Keywords: Birthday parties -- Juvenile fiction; Gifts -- Juvenile fiction; Horror tales; Scholarships -- Juvenile fiction; Birthday parties -- Fiction; Gifts -- Fiction; Scholarships -- Fiction; Horror fiction